#TITLE_ALTERNATIVE# - SYAHRIAL (NIM 26997011); Pembimbing: James McElvaney, PhD, BE., CEng., MICE., Dr.Ir. Bambang Suge, M.
Continuously-graded asphalt concrete has good resistance to permanent deformation, but is less resistant to cracking. When asphalt concrete is used as a pavement surface layer (new construction or overlay), the predominant failure mode is cracking, not deformation. One way of possibly strengthening the asphalt layer is by using a geotextile. Use of a geotextile in the asphalt layer is expected to reduce strain or deflection so that a thinner than conventional asphalt layer can be used or alternatively a longer pavement service life can be achieved at the same thickness. The main objective of this investigation was to evaluate the laboratory fatigue characteristics of asphalt concrete specimens without and with a geotextile using the Eartec machine. The tests were conducted in the controlled-stress sinusoidal loading mode using the four-point bending flexural fatigue test. Only one geotextile type i.e. Trevira Spunbond 011140 and one location i.e. 1 an from the bottom of the specimen was investigated. All tests were carried out at room temperature. The parameters used to evaluate the fatigue characteristics of asphalt concrete without and with a geotextile were the number of cycles to failure and the effectiveness factor, the initial strain and initial stiffness, the number of cycles for crack initiation and propagation, and the cracking mechanism. The results of the investigation indicated that including a geotextile in the asphalt concrete improved its fatigue characteristics. The effectiveness factor, i.e. the ratio of the number of cycles to failure for specimens with and without a geotextile at a given stress level ranges from 6.01 to 8.83. The inclusion of a geotextile in asphalt concrete appears not to influence the initial stiffness and strain. The initial stiffness ratios between the asphalt concrete with and without a geotextile is 1.07 and the initial strain ratio ranges from 0.95 to 0.98. The ratio of the number of cycles for crack propagation for the asphalt concrete with and without a geotextile, ranges free 38.74 to 43.37. The number of cycles to crack initiation is also greater for specimens with a geotextile. Analysis of the cracking mechanise in the asphalt concrete with a geotextile showed that crack propagation was arrested by the geotextile before propagating upward to the surface.